COVID-19 epidemic phases and morbidity in different areas of Chinese mainland, 2020 - Wang, Yuehai; Yu, Jinghong; Wang, Fei; Zhang, Yuqiang; Ma, Shengjun (Frontiers in Public Health, 2023)
Background. In the early stage of COVID-19 epidemic, Chinese mainland once effectively controlled the epidemic, but COVID-19 eventually spread faster and faster in the world. The purpose of this study is to analyze the possible factors affecting the occurrence and development of COVID-19 epidemic in Chinese Mainland in 2020. Methods. We divided the Chinese mainland into areas I (Wuhan city), II (Hubei province, excluding Wuhan) and III (Chinese mainland, excluding Hubei). We divided the epidemic process into phases I to IV: limited patient, accelerated increase, decelerated increase and containment phases. We also combined phases II and III as outbreak phase. We tracked and compared the epidemic data in different phases and areas in 2020. Results. The worst epidemic area in Chinese mainland before March 18, 2020 and after June 15, 2020 was area I and area III respectively. Area I alone had a long case clearing period of 17 days in phase IV. In Wuhan, human COVID-19 infection might occur before December 8, 2019, while the outbreak phase might occur before January 16 or even 10, 2020. Conclusions. Insufficient understanding of COVID-19 hindered the implementation of early effective isolation measures, leading to COVID-19 outbreak in Wuhan, and strict isolation measures were effective in controlling the epidemic. The import of foreign COVID-19 cases has made it difficult to control the epidemic of area III. when we again suffer from infectious diseases with unclear transmission routes, we should first take strict isolation measures, which of course also requires corresponding laws to comply with. In the process of combating the epidemic, mutual cooperation may be the only choice for mankind.